Numerical investigations on flashback dynamics of premixed methane-hydrogen-air laminar flames - YILMAZ, BARIŞ (My University, 2022)
Injecting hydrogen into the natural gas network to reduce CO2 emissions in the EU residential sector is considered a critical element of the zero CO2 emissions target for 2050. Burning natural gas and hydrogen mixtures has potential risks, the main one being the flame flashback phenomenon that could occur in home appliances using premixed laminar burners. In the present study, two-dimensional transient computations of laminar CH4- + air and CH4 + H-2 + air flames are performed with the open-source CFD code OpenFOAM. A finite rate chemistry based solver is used to compute reaction rates and the laminar reacting flow. Starting from a flame stabilized at the rim of a cylindrical tube burner, the inlet bulk velocity of the premixture is gradually reduced to observe flashback. The results of the present work concern the effects of wall temperature and hydrogen addition on the flashback propensity of laminar premixed methane-hydrogen-air flames. Complete sequences of flame dynamics with gradual increases of premixture velocity are investigated. At the flame flashback velocities, strong oscillations at the flame leading edge emerge, causing broken flame symmetry and finally flame flashback. The numerical results reveal that flashback tendency increase with increasing wall temperature and hydrogen addition rate. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; KİMYA, FİZİKSEL; Temel Bilimler (SCI); ELEKTROKİMYA; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); ELECTROCHEMISTRY; ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); Yüzeyler ve Arayüzler; Yüzeyler, Kaplamalar ve Filmler; Genel Mühendislik; Mühendislik (çeşitli); Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fiziksel ve Teorik Kimya; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Surfaces and Interfaces; Surfaces, Coatings and Films; General Engineering; Engineering (miscellaneous); Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical and Theoretical Chemistry; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Laminar premixed flames; Flame flashback; Hydrogen; Methane; Numerical simulations; OpenFOAM; BOUNDARY-LAYER FLASHBACK; PROPAGATION; COMBUSTION; PRESSURE